(untitled) (Marketing Journal, 2025)
This article examines the impact of pandemics and crises on social sectors. The article analyzes the definitions and types of social sectors, their importance during pandemics and crises, emerging problems and ways to overcome them. Based on the 305 analysis of the literature, the main trends in the impact of pandemics and crises on social sectors are identified. The article also provides recommendations for supporting social sectors, anti -crisis measures and future research.